The effect of certain elements on the skin characteristics and yield of the red McClure potato - Sparks, Walter C., author; McLean, John G. (John Grim), 1913-, advisor; Kreutzer, William A., committee member; Romine, Dale Servetus, committee member; Binkley, A. M. (Almond Madison), 1900-, committee member (Colorado State University. Libraries, 1943)
To view the abstract, please see the full text of the document.
Keywords: Potatoes -- Breeding; Growth (Plants); Plant growth promoting substances; Plant growth inhibiting substances